The Physical, Chemical, Microbiological, Antibacterial and Prebiotic Characteristics of Fermented Porang Flour with Addition of Bacteria and Yeast (Biosaintifika: Journal of Biology & Biology Education, 2024)
Porang (Amorphophallus oncophylus) tubers are one of the export commodities due to their glucomannan content. This study aimed to investigate the characteristics of water fermentation and the quality of porang fermented flour with the addition of Lactobacillus plantarum (LP), Bacillus subtilis (BS), and Saccharomyces cerevisiae (SC). Fermentation was conducted using four treatments, namely LP+BS, LP+SC, BS+SC which consisted of 10%v/v of inoculum, respectively, and LP+BS+SC which consisted of 7%v/v LP, 7% BSv/v, and 6%SCv/v. During fermentation, pH, total acidity, and total microorganisms were observed. Proximate, glucomannan content, starch content, fiber content, and antibacterial and prebiotics characteristics were observed for fermented porang flour. The results showed that pH decreased while total acidity increased during fermentation. Total aerobic bacteria had the highest population at 24 hours of fermentation while lactic acid bacteria had the highest population at 24- and 48-hour fermentation. Yeast reached the highest population at 72 hours of fermentation. Porang fermented flour with the addition of BS+SC contained the highest glucomannan content, carbohydrate, and fiber content. Moreover, the flour with BS+SC had an antibacterial effect against Escherichia coli and Staphylococcus aureus and supported the growth of Lactobacillus acidophilus. Porang fermented flour which is processed with the addition of a mixed culture of BS and SC can be developed to improve the nutrititional and functional properties of porang flour.